(untitled) (PETITUM, 2025)
This study examines legal protections for teachers in State Elementary Schools in Luwu Timur Regency, focusing on preventing discrimination regarding criminal sanctions when disciplining students. Using empirical legal research, the study evaluates whether existing frameworks—specifically Law No. 14/2005 (Teachers and Lecturers) and Law No. 20/2003 (National Education System)—effectively shield educators from criminalization. The findings reveal that while these laws theoretically guarantee professional security and legal certainty, practical implementation remains inconsistent. Teachers frequently face vulnerability when disciplinary actions are misinterpreted as abuse, indicating that current legal protections lack sufficient effectiveness. Consequently, the research highlights a critical need for clearer, more robust legal mechanisms and dedicated legal assistance for educators. Furthermore, the study analyzes the application of the Criminal Code (KUHP) and child protection regulations in cases where disciplinary measures are deemed excessive. It concludes that while criminal sanctions remain applicable for physical or psychological violence, there is an urgent necessity for specific technical regulations. Clearer guidelines are essential to distinguish between legitimate educational discipline and prohibited violence, thereby safeguarding teachers from excessive criminalization while simultaneously upholding the fundamental rights and well-being of students.